Data-driven smallholder tea production in Uganda - Owoyesiga, Hamlus (Technical Centre for Agricultural and Rural Cooperation, 2018)
A spatial data management system to profile tea farmers and map tea plots among members of the Igara Tea Growers Factory (IGTF) in Uganda has led to increased access to financial services for producers, and higher repayment rates for input loans. An immediate impact has been increased productivity and a dramatic fall-off in the practice of side-selling – so much so that other tea companies are now considering adopting the model.